Strategi Manajemen Sumber Daya Manusia dalam Badan Amil Zakat Nasional Kota Pontianak, Provinsi Kalimantan Barat (Periode 2020-2024) - Fatmawati, Fatmawati; Firayanti, Yuni; Marhamah, Marhamah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze the human resource management (HRM) strategy implemented by the National Amil Zakat Agency (BAZNAS) of Pontianak City during the 2020–2024 period, as well as to identify various internal and external factors. The approach used in this research is descriptive qualitative, with data obtained through primary sources such as interviews and direct observations, as well as secondary data in the form of relevant documents. Data collection was carried out using field observation techniques, in-depth interviews with relevant parties, and documentation. Furthermore, the data analysis process included data reduction, data presentation, and drawing conclusions. The validity of the data was ensured through the application of triangulation of sources, techniques, and time. The findings show that the HR strategy focuses on workforce planning, an open and needs-based recruitment and selection system, specialized training (including at the national BAZNAS), collection and distribution management, regular performance evaluations, and motivation based on non-financial rewards and team solidarity. The management is supported by strong internal cohesion and national regulations but faces obstacles such as a limited number of staff and a lack of public understanding. Internal supporting factors for HR management include team spirit, solidarity, and leadership that is open to feedback. Meanwhile, external supporting factors include regulations and policies from the National BAZNAS and the Ministry of Religious Affairs, national-level training, support from local government, and increasing public awareness of the importance of zakat. These findings highlight the need to strengthen HR capacity and public communication to enhance the effectiveness of zakat management and the sustainability of BAZNAS Pontianak City's social services.